An optimized fringe generator of 3D pavement profilometry based on laser interference fringe. (January 2021) - Chu, Chu; Wang, Linbing; Yang, Hailu; Tang, Xiaocong; Chen, Qiyao
Highlights: This paper has employed laser interference fringe on 3D pavement profilometry. This study optimizes the configuration of the fringe generator. The new fringe generator can emit interference fringes with higher frequencies. The optimized fringe generator makes it possible to measure the 3D pavement profile. The laser interference fringe based-3D pavement profilometry achieves high accuracy. Abstract: As pavement distresses have more negative influences on the driving safety and comfortableness, pavement distress detection and maintenance becomes more significant. 3D pavement profilometry can help analyze the type and severity of the pavement distress, which provides a basis for pavement maintenance. This paper has employed laser interference fringe on 3D pavement profilometry. This new technology has great research value and prospect on improving the measurement accuracy.However, the fringe generators used in previous 3D profilometry technologies performed close-range projection (< 1 m) with laser interference fringe on the object surfaces being measured which have small sizes (diameter < 0.1 m), so the area of the fringe region was small.To extract the 3D profile information of the pavement surface, it is imperative to increase the projection distance to enlarge the area of fringe region. However, increasing the projection distance will cause the fringe spatial frequency and the measurement accuracy to decrease.In order to solve the problem, this study optimizes the configuration of the fringe generator based on previous researches, that enables it to emit interference fringes with higher spatial frequencies. It is proved that the new fringe generator makes it possible to extract the 3D pavement profile.After validation, the results show that the measurement error reaches ±0.38 mm when the fiber core interval is 0.75 mm and the projection distance is 1200 mm.